Overgrowth of a Mouse Model of the Simpson–Golabi–Behmel Syndrome Is Independent of IGF Signaling - Chiao, Eric; Fisher, Peter; Crisponi, Laura; Deiana, Manila; Dragatsis, Ioannis; Schlessinger, David; Pilia, Giuseppe; Efstratiadis, Argiris (Developmental biology, 2002)
The type 1 Simpson–Golabi–Behmel overgrowth syndrome (SGBS1) is caused by loss-of-function mutations of the X-linked GPC3 gene encoding glypican-3, a cell-surface heparan sulfate proteoglycan that apparently plays a negative role in growth control by an unknown mechanism. Mice carrying a Gpc3 gene knockout exhibited several phenotypic features that resemble clinical hallmarks of SGBS1, including somatic overgrowth, renal dysplasia, accessory spleens, polydactyly, and placentomegaly. In Gpc3/ΔH19 double mutants (lacking GPC3 and also carrying a deletion around the H19 gene region that causes bialellic expression of the closely linked Igf2 gene by imprint relaxation), the Gpc3-null phenotype was exacerbated, while additional SGBS1 features (omphalocele and skeletal defects) were manifested. However, results from a detailed comparative analysis of growth patterns in double mutants lacking GPC3 and also IGF2, IGF1, or the type 1 IGF receptor (IGF1R) provided conclusive genetic evidence inconsistent with the hypothesis that GPC3 acts as a growth suppressor by sequestering or downregulating an IGF ligand. Nevertheless, our data are compatible with a model positing that there is downstream convergence of the independent signaling pathways in which either IGFs or (indirectly) GPC3 participate.